NON GENETIC FACTORS EFFECT ON REPRODUCTIVE PERFORMANCE AND PREWEANING MORTALITY FROM ARTIFICIALLY AND NATURALLY BRED IN BALI CATTLE - A. Gunawan; R. Sari; Y. Parwoto; M.J. Uddin (Diponegoro University, 2011)
The aim of this study was to evaluate effect of non genetic factors on reproductive performance ofBali cattle. Data on reproduction performance were collected from Breeding Centre of Bali Cattle inDenpasar-Bali. Reproductive traits studied were age at first calving (AFC), calving interval (CI) andpregnancy rate (PR). To observe the effect of non genetic factors on the reproductive traits, a mixedmodel was used because all of the traits studied were measured repeatedly in individuals. The overallmeans for AFC, CI, PR and preweaning mortality were 43.86±0.70 months, 360.93±4.47 days,88.44±1.91% and 7.58±1.07%, respectively. The results showed that AFC and PR were significantly(P<0.01) influenced by dam year of birth but mating system had no significant (P>0.05) effect. Withregard to CI, dam year of birth and parity affected CI while mating system had no significantly affect(P>0.05) on CI. The preweaning mortality was only affected by the age of dam significantly (P<0.01).The average of reproductive performance and preweaning mortality in Bali Cattle were not dependedremarkably on the mating system being practiced. It might be concluded that an improvement in Balicattle reproductive traits is possible through improving management systems and utilisation ofcontrolled breeding techniques.